Diffraction of Modulated Electromagnetic Impulses on Periodical Grating - Gavrilova, T.V.; Sidorenko, Yu.B. (Радиофизика и радиоастрономия, 2002)
The problem of diffraction of amplitude-modulated impulses with linear frequency modulation on the planar periodical grating consisting of infinitely thin and ideally conducting strips has been considered. The ability to provide the group impulse delay without distorting of their forms and changing their duration has been shown. Dependencies of group delay on grating parameters and the velocity of frequency change in the field of long waves have been given. Рассмотрена задача дифракции амплитудно-модулированных импульсов с линейной частотной модуляцией на ленточной периодической решетке, состоящей из бесконечно тонких и идеально проводящих лент. Показано, что возможно осуществить групповую задержку сигналов без искажения их формы и изменения длительности. Приведены зависимости групповой задержки от параметров решетки и скорости качания частоты в длинноволновой области. Розглянуто задачу дифракції амплітудно-модульованих імпульсів з лінійною частотною модуляцією на стрічковій періодичній ґратці, що складається з нескінченно тонких та ідеально провідних стрічок. Показано, що існує можливість створити групову затримку сигналів не змінюючи їх форму та тривалість. Наведено залежності групової затримки від параметрів ґратки та швидкості качання частоти у довгохвильовій області.